A study on solar disinfection of drinking water using flat-plate solar collector - Donasco, Edgar Alan A. (2000)
Lack of access to a reliable steady supply of safe drinking water remains a problem for developing countries like the Philippines. A treatment method that is simple, low-cost, effective, and sustainable needs to be in place as an alternative.